MEASURING OF CYTOKINES TNF-Α AND IFN-Γ CONCENTRATION LEVELS IN ASTHMA PATIENTS - Abd-alameer, Ali Mohammed (Antis-Publisher, 2025)
Objective: Asthma is a chronic inflammation of the Pulmonary air passages, Many cells and cellular elements play a significant part in its occurrence, especially T lymphocytes. This inflammation in sensitive individuals causes frequent symptoms such as coughing, difficulty breathing, and asthma disease is characterized by increased immune overresponse in the bronchi, affected by several triggers, including inflammatory cytokines, which are crucial in the development of asthma. These include cytokines the TNF-α and IFN-γ, which contribute to the excessive immune response of the Bronchial passages leading to bronchonchial contraction. This study aimed to the Measurement of immunological standards TNF-α and IFN-γ in the serum of asthma patients and to study the extent of the effect of these two cytokines in increasing the severity of the disease and understanding the specific roles of these cytokines in the development of asthma and its pathological mechanisms. Method: 60 samples were collected from asthma patients who are reviewing the Allergy and Asthma Center in Marjan hospital in Babylon governorate and 40 healthy people who were used as a control group. Immunoassays were conducted for blood serum samples collected from patients and healthy patients by enzyme-linked immunoadsorption to measure TNF-α and IFN-γ. Results: showed that there was a moral increase TNF-α and IFN-γ levels in serum of asthma patients (p<0.05) while the concentrations of immunological standards in the control group serum decreased. Novelty: According to the this study, asthma patients have an increase in the concentrations of TNF-α and IFN-γ in their serums compared to the serum of the control group,Which serves to shed new light on the role of these two cytokines in the exacerbation of asthma, in order to manufacture inhibitory drugs that target them.